Kinetics of tissue oxygenation index during fast and slow cardiopulmonary bypass initiation - Turra, Jan; Bauer, Adrian; Möbius, Andreas; Wojdyla, Jacob; Eisner, Christoph (Perfusion, 2023)
IntroductionDespite being a daily clinical application in cardiac operating theaters, an evidence-based approach on how to optimally initiate the heart?lung machine (HLM) to prevent critical phases of cerebral ischemia is still lacking. We therefore designed a study comparing two different initiation times for starting the cardiopulmonary bypass (CPB).MethodsWe conducted a monocentric, randomized, and prospective study comparing the impact of two initiation times, a rapid initiation of 15 s and a slow initiation of 180 s to reach the full target flow rate of 2.5 L/min/m2 times the body surface area, on cerebral tissue oxygenation by near infrared spectroscopy measurements.ResultsThe absolute values in tissue oxygenation index (TOI) showed no difference between the groups before and after the CPB with a 10% drop in oxygenation index in both groups due to the hemodilution through the HLM priming. Looking at the kinetics a rapid initiation of CPB produced a higher negative rate of change in TOI with a total of 21% in critical oxygenation readings compared to 6% in the slow initiation group.ConclusionIn order to avoid critical phases of cerebral ischemia during the initiation of CPB for cardiac procedures, we propose an initiation time of at least 90 s to reach the 100% of target flow rate of the HLM.